IMPLEMENTASI LATIHAN MIRROR THERAPY TERHADAP RENTANG GERAK (ROM) PADA PASIEN DENGAN FRAKTUR HUMERUS DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Tasya Dwi Andini; Suharto Suharto; Kipa Jundapri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Humerus fracture is an upper arm bone fracture that causes limited range of motion (ROM) and pain. One non-pharmacological intervention to improve ROM is mirror therapy, a training method using visual illusion to stimulate the central nervous system, thereby helping to enhance mobility and reduce pain. The purpose of this study was to describe the implementation of mirror therapy in patients with humerus fractures at TK II Putri Hijau Hospital, Medan. This research used a descriptive case study method with a medical-surgical nursing care approach, starting from assessment, diagnosis, intervention, implementation, and evaluation. The study was conducted on two post- operative humerus fracture patients in a ±3-week recovery period who had been referred to physiotherapy, were over 18 years old, and had no contraindications to performing mirror therapy exercises. The therapy was carried out for one week with three sessions. The results showed an improvement in ROM in Patient 1, with an increase in extension (from 40° to 44°) and adduction (from 30° to 34°). In Patient II. improvement was seen in extension (from 45° to 50°) and adduction (from 30° to 35°). In conclusion, mirror therapy has been proven to help improve range of motion and reduce pain in patients with humerus fractures. This therapy shows positive effects when combined with conventional physiotherapy.